1612. Evaluation of the Use of Ceftolozane/Tazobactam for the Treatment of ESBL-producing Enterobacterales Infections Using International Data from SPECTRA (Study of Prescribing Patterns and Effectiveness of Ceftolozane/Tazobactam Real World Analysis). (31st December 2020) - Soriano, Alex; Puzniak, Laura A; Bassetti, Matteo; Kaul, Sundeep; Moise, Pamela; Paterson, David; Paterson, David
Abstract: Background: There is a paucity of data on outcomes of patients with severe ESBL-producing Enterobacterales infections treated with empiric or directed ceftolozane/tazobactam (C/T). This study looked at the treatment patterns and outcomes associated with C/T use in the treatment of ESBL-producing Enterobacterales. Methods: Data were collected from an international cohort of 32 hospitals in 6 countries as part of SPECTRA, a retrospective multicenter database of C/T use globally, from 2016 – 2019. All adult patients with an ESBL positive Enterobacterales sterile site culture and treated with ≥ 48 hours of C/T were eligible. Outcomes assessed were clinical success, 30-day mortality from index event and readmission. Results: There were 59 patients with 121 ESBL positive isolates. Blood and urine were the most common sites of infection at 19.8% each, followed by respiratory (18.2%). E. coli (50%) and K. pneumoniae (30%) were the most common pathogens. On average patients had 2 positive ESBL isolates; median 1; range 1-15. Most patients had the same infection site and ESBL pathogen, however 13 had multi-site ESBL pathogens identified and only 2 had polymicrobial ESBL pathogens. Septic shock was observed in 14 (24%) patients; 29 (49%) were in the ICU at the onset of infection. The most common comorbid conditions were immunocompromised hosts (37%) and cardiac disease (32%). 29% of patients were transplant recipients, and 28% had a CrCl < 50 ml/min. In most patients (71%), C/T was given as directed therapy (i.e., once culture results were available). C/T was given prior to culture results (i.e., as empiric therapy) in 17 (29%) patients, of which 77% had clinical success. C/T dose was 1.5 g in 49%. Only 2 of 10 patients with a respiratory source received the currently licensed 3 g dose. Overall, clinical success was observed in 36 (61%) patients. 30-day mortality was 12%. Readmissions occurred in 5%, of which 2 were infection related. Conclusion: The role of newer non-carbapenem antibiotics in the treatment of severe ESBL infections is currently undefined. In a multinational patient database, C/T was found to be effective in severe infections caused by ESBL-producing Enterobacterales . Prospective studies are needed to further define the role of C/T in the setting of frequent drug-resistant Gram-negative pathogens. Disclosures: Laura A. Puzniak, PhD, Merck (Employee) Matteo Bassetti, MD, Shionogi Inc. (Advisor or Review Panel member) Pamela Moise, PharmD, Merck & Co., Inc. (Employee, Shareholder) David Paterson, Accelerate (Speaker's Bureau)BioMerieux (Speaker's Bureau)BioMerieux (Advisor or Review Panel member)Entasis (Advisor or Review Panel member)Merck (Advisor or Review Panel member)Merck (Grant/Research Support)Merck (Speaker's Bureau)Pfizer (Speaker's Bureau)Shionogi & Co., Ltd. (Grant/Research Support)VenatoRx (Advisor or Review Panel member)